2017
DOI: 10.1504/ijbex.2017.080606
|View full text |Cite
|
Sign up to set email alerts
|

A study on customer's perception of online banking and e-service quality among Chennai customers

Abstract: Abstract:The information technology advancements in India have more impact on Indian banking industry. Now, the internet is the most preferred medium which is used between customer and the bank. Due to technological advancements in India, the internet availability and the internet usage is increased largely. The internet medium is rapidly changing the traditional face to face banking to online banking. To study the quality of the bank, it is necessary to study the e-service quality of banks. This paper deals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Many studies have demonstrated that BCs and BFs can support traditional banks in offering financial services in branchless locations. According to Kumar and Sharma (2017), branchless banking is one of the alternative banking channels that is increasingly important for providing customers with financial services. They also opined that using banking agents can help financial institutions reach more people in remote places by enabling clients to perform simple banking operations without the requirement for a physical branch.…”
Section: Research Gap Research Questions and Hypothesesmentioning
confidence: 99%
“…Many studies have demonstrated that BCs and BFs can support traditional banks in offering financial services in branchless locations. According to Kumar and Sharma (2017), branchless banking is one of the alternative banking channels that is increasingly important for providing customers with financial services. They also opined that using banking agents can help financial institutions reach more people in remote places by enabling clients to perform simple banking operations without the requirement for a physical branch.…”
Section: Research Gap Research Questions and Hypothesesmentioning
confidence: 99%
“…It turned into counseled that banks deal with strengthening those additives of provider best so one can enhance e-client delight and loyalty within the "Indian e-banking region". Kumar and Shenbagaraman (2017) explored customer perceptions of the effectiveness of e-offerings and online banking in Chennai, India. They determined that service satisfactory has a good-sized impact on client loyalty and pride in on-line banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dimensions such as compensation and recovery, access, personalization and assurance are the major contributors to customer satisfaction for e-banking services and are considered the dimensions major for defining the service quality for online banking services [40]. The Impact of charges fees for e-banking services have shown a negative impact on the deductions, and charges counted for the listed services in e-banking as negatively contributing towards customer satisfaction [41].…”
Section: B Literature Depiction For Pricing and Rewards Toward Custom...mentioning
confidence: 99%